RELATIONSHIP BETWEEN PARENTING STYLE AND PERCEIVED INFORMATION SOURCES WITH STUNTING AMONG CHILDREN - Melinda Restu Pertiwi; Pudji Lestari; Elida Ulfiana (International Journal of Nursing and Health Services (IJNHS), 2019)
Stunting is the condition of chronic malnutrition during the most critical growth period at the beginning of life, which is characterized by height according to age <-2 elementary school. The behavior of mothers taking care of children can be influenced by technology, which is characteristic of millennial generations. The study aimed to describe the mothers’ behavior who have children with stunting experience. Method: this study is a descriptive study with a sample of 174 respondents with a cluster random sampling technique in millennial generation mothers in the Martapura Kota Subdistrict, Banjar Regency, South Kalimantan. Results: The results of the study showed that a mother's parenting style in stunting children was mostly negative, and most of the information access of mothers was productive. Conclusion: Negative parenting increases the risk of stunting in children, whereas access to productive information reduces the risk of stunting in children. Nurses are expected to provide health promotion about the understanding, causes, and effects of stunting on children so that they can change parenting to be positive and access information about productive millennial mothers. Keywords: behavior millennial mother, stunting, child